2018
DOI: 10.1111/inm.12481
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the suicidal person: A Delphi study of what characterizes a recovery‐oriented caring approach

Abstract: More research is needed for supporting mental health nurses in their caring for suicidal individuals. This study aimed to describe what characterizes a recovery-oriented caring approach, and how this can be expressed through caring acts involving suicidal patients and their relatives. Delphi methodology was used, and research participants were recruited as experts by experience to explore a recovery-oriented caring approach in a dialogical process between the experts and the researchers. The results highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
14
0
2
Order By: Relevance
“…Three studies (Dawson et al, 2019; Gandi & Wai, 2010; Sellin et al, 2019) applied models of care based on a relational conceptualization of recovery: Open Dialogue (Olson et al . 2014), Partnerships‐in‐Coping (Shanley et al, 2003) and Recovery‐Oriented Care Approach (ROCA; Sellin et al, 2018). Relational recovery reflects the ideology that humans are interdependent, and the social context defines the experience (Price‐Robertson et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies (Dawson et al, 2019; Gandi & Wai, 2010; Sellin et al, 2019) applied models of care based on a relational conceptualization of recovery: Open Dialogue (Olson et al . 2014), Partnerships‐in‐Coping (Shanley et al, 2003) and Recovery‐Oriented Care Approach (ROCA; Sellin et al, 2018). Relational recovery reflects the ideology that humans are interdependent, and the social context defines the experience (Price‐Robertson et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Partnership‐in‐Coping combines a recovery‐oriented approach with the use of the therapeutic alliance, to support service users to develop biophysiological, cognitive‐emotional, social, and emotional coping (Shanley et al, 2003). ROCA is an approach to working with people experiencing suicidal ideation, which focuses on their recovery process rather than monitoring behaviour (Sellin et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the external recovery process described how consumers are presented in the external world without being affected by symptoms of mental illness or living life in the community like everyone else (Jacob et al 2015). Six studies classified the external recovery process according to attributes such as social inclusion, relationship, and attaining an optimum level of functioning in the community (Gaffey et al 2016; Gilburt et al 2013; Jackson‐Blott et al 2019; Jacob et al 2015; Karpetis 2018; Parker et al 2017; Sellin et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies described several factors that can expedite the personal recovery process of consumers. These factors include collaborative or multidisciplinary teamwork, therapeutic rapport, good communication skills (Gaffey et al 2016; Karpetis 2018; Sellin et al 2018), showing ‘empathy, the ability to listen’ (Gaffey et al 2016), caring, helping, supporting, being respectful and open (Gilburt et al 2013), assessing risk (Karpetis 2018), and consumer involvement in service utilization (Gilburt et al 2013). In addition, two studies recommended factors such as staff involvement and developing idiosyncratic management strategies in delivering recovery‐oriented services (Gilburt et al 2013; Jackson‐Blott et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…From the relatives’ perspectives, participation was about being actively involved in a process in which the person regains the desire to live (Sellin, Asp, Kumlin, Wallsten, & Wiklund Gustin, 2017b). The results from these studies (Sellin et al, 2017a, 2017b) were the point of departure when designing a Delphi-study, to which researchers in suicide prevention, registered nurses, and representatives from a Swedish organization working with suicide prevention and support to relatives, were invited to give their perspectives and reflect on what characterizes a recovery-oriented caring approach (ROCA) (Sellin, Kumlin, Wallsten, & Wiklund Gustin, 2018). The Delphi-panel concluded that such a caring approach needs to support patients in giving voice to their perspectives in dialogue with mental health nurses in what can be understood as a “communicative togetherness.” This means that the communication between the patient and the nurse is recognized as essential and needs to take place and evolve in relation to the patient’s lifeworld.…”
Section: Introductionmentioning
confidence: 99%